THE INCIDENCE OF REPRODUCTIVE DISORDERS IN A DAIRY HERD: A CASE STUDY IN SINJAI REGENCY - M. Yusuf; L. Rahim; . Hasbi; N. Aliah (Jurnal Ilmu dan Teknologi Peternakan, 2012)
The objective of this study was to ascertain the incidence of reproductive disorders in a dairy herd. A total of 44 Holstein Friesian cows in a dairy herd were enrolled in the present study. Trans-rectal palpation of the uterine was performed to determine the consistency of uterine including contraction, elasticity, tonicity, symmetry of uterine horns, and the presence of any fluid in the uterus followed by the presence of any palpable ovarian structures. Cows that did not become pregnant during clinical examination were examined vaginoscopically. Data obtained in the present study were analyzed descriptively based on percentages and means. T-test was used to analyze the interval from calving to first artificial insemination (AI) between cyclic cows and cows with reproductive disorders. The results of this study showed that incidence of reproductive disorders was very high; 38.6%. Inactive ovaries, cyst, and endometritis were the most reproductive disorders suffering the dairy cows. These reproductive disorders subsequently reduced reproductive performance by prolonged interval from calving to first AI as well as interval from calving to pregnancy. Lower BCS of the cows were invented as the most prominent causes of this issue.